Interpersonal Victimization During Childhood and Adolescence and Educational Attainment in Young Adulthood: A Latent Class Analysis Approach - Frøyland, Lars Roar (Journal of interpersonal violence, 2023)
Previous research relates violent victimization early in life to a wide range of unfavorable outcomes in adulthood, among them a lack of educational attainment. A tendency to conduct separate investigations into violent victimization in different areas of life has so far hampered our understanding of both overall victimization processes and its outcomes. The present study overcomes this issue by investigating the cumulative burden of violent victimization during childhood and adolescence as well as the associations between victimization and educational attainment in young adulthood. The study uses a nationally representative sample of 18 to 19-year-old Norwegian students (n = 3,160) from the school-based UngVold 2007 survey, merged with information from official registers up to 2016 (age 27–28). Using latent class analysis (LCA), we combine retrospective accounts of experiences with parental, peer, and sexual violence during childhood and adolescence with educational attainment in young adulthood. The analyses reveal five classes of violent victimization: (1) non-victims (55.7%), (2) peer victims (16.6%), (3) victims of parental violence (14.5%), (4) victims witnessing domestic violence (5.6%), and (5) polyvictims (experiencing parental, peer, and/or sexual violence: 7.6%). They also show lower educational attainment in all groups reporting victimization through physical contact compared to non-victims, particularly among peer victims and polyvictims. Violence thus seems to impair educational attainment for a large share of the population. The identification of particularly lower education among the polyvictims also show the importance of considering the cumulative burden of violence when deciding on treatment needs and the design of help services for victims.